Desarrollo de un protector ocular para fototerapia en recién nacidos: Una tecnología - Silva, Lucía [UNESP]; Da Silva, Fernanda Sotrate [UNESP]; Turiani, Mariana [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Spiri, Wilza Carla [UNESP] (FapUNIFESP (SciELO), 2008)
Hyperbilirubinemia results from the predisposition of newborns to produce bilirubin and their ability to excrete it. The treatment applied is phototherapy; however, one of its complications is degeneration of the retina by exposure to light, making it essential to provide proper eye protection. The objective of this study is to describe the development of an invention (utility model patented) for eye protection in newborn phototherapy. This invention aims to replace the current widespread practice of using improvised means that are uncomfortable for the baby and disrupt the mother/child relationship. A study was made of the radiances emitted by light sources used in phototherapy. The invention consists of an eye protector model for use during the newborn's phototherapy, allowing greater closeness between mother and baby. The device is easy to use, economical, removable and appropriate for newborns, causing no discomfort, and its effectiveness has been proved through radiance tests.
Development of an eye protector for phototherapy on newborns: A technology
Keywords: Newborn; Nursing; Phototerapy; Technology